KESAHIHAN DIAGNOSTIK HEMOGLOBIN RETIKULOSIT UNTUK DETEKSI DEFISIENSI ZAT BESI DI KEHAMILAN (Diagnostic Validity of Reticulocyte Hemoglobin for Iron Deficiency Detection in Pregnancy) - Tri Ratnaningsih; Budi Mulyono; Sutaryo Sutaryo; Iwan Dwiprahasto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Entering the second trimester of pregnancy, more iron is required due to the increase in erythrocyte mass, plasma volume andthe development of fetus as well as chorion. Iron is needed the most in the third trimester. The existing hematological iron stageparameters can only detect iron deficiency in the latest stage. The aim of this study was to know the assessment validity of Ret-Heexamination as a new parameter to diagnose iron deficiency in pregnant women with anemia, as well as a screening tool for those interm pregnancy without anemia. The research design was cross sectional. The subjects were women in term pregnancy, gathered fromPKU Muhammadiyah Hospital, Bantul Yogyakarta from May to November 2013. A seven (7) mL blood sample was taken from thecubital vein of the subjects. Two mL of the sample was tested for routine hematological examination using an EDTA tube, while theRet-He was assessed using an automatic hematological instrument Sysmex XT-2000-i (Symex Corporation, Kobe, Japan). The serumof the remaining five (5) mL was used to check the serum iron and TIBC to obtain the saturation value (Tsat) using Cobas analyzerC501 (Roche Diagnostics, Germany), while the serum ferritin (SF) was examined using Minividas. The subjects were classified into two(2) groups based on the Hb levels, namely: anemia (Hb<11 g/dL) and those who did not (Hb≥11 g/dL). Furthermore, they were alsoclassified into two (2) groups based on transferrin saturation values: iron deficient (Tsat <9%) and normal (Tsat ≥9%). From 291subjects, 59 (20.3%) were found to have anemia and 232 (79.7%) did not. The cut off value of Ret-He to diagnose iron deficiency inpregnant women with anemia was 29.8 pg (82% sensitivity and 72% specificity). Meanwhile, the cut-off value of Ret-He for irondeficiency screening in pregnant women without anemia was 29.8 pg, with a sensitivity and specificity of 92% and 87% respectively.The Ret-He holds a good diagnostic validity to detect iron deficiency in pregnancy, with or without anemia.